Mineralization of Natural Hydroxyapatite for High Efficiency of Pb2+ion Removal in Aqueous Solution - Xuan Vuong, Bui (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2, 2019)
Abstract: The mineralized hydroxyapatite (m-HA) was prepared by soaking natural hydroxyapatite (n-HA) extracted from pig bone in the simulated body fluid (SBF) for 3 days. The m-HA was much better in comparison with the n-HA for removing Pb 2+ ions from aqueous solution. After 4 hours of adsorption experiments, m-HA material eliminated almost 100% of lead ions while n-HA removes only 65.4%. The adsorption isotherm study was effectuated for the m-HA. The experimental data was fitted for both Langmuir and Freundlich models in which the Langmuir model was more suitable due to the higher value of R 2 coefficient. The maximum adsorption capacity (Q m ) of Pb 2+ ions on the m-HA was calculated from the Langmuir isotherm equation, which was the high value of 574.1 (mg/L). The mechanism of lead ion removal for m-HA was determined by XRD analysis. The obtained result highlighted the ion exchange between the m-HA and the Pb 2+ ions. Keywords: Natural hydroxyapatite (n-HA), mineralized hydroxyapatite (m-HA), Pb 2+ , SBF, removal. References [1] S.A. Alrumman, A.F. El-kott, M.A. Kehsk, Water pollution: Source and treatment, Am. J. Environ. Eng. 6 (2016) 88-98. https://doi.org/ 10.5923/j.ajee.20160603.02. [2] F. Fu, Q. Wang, Removal of heavy metal ions from waste waters: A review, J. Environ. Manag. 92 (2011) 407-418. https://doi.org/10.1016/j. jenvman.2010.11.011. [3] W. Zhang, F.H. Wang, P.L. Wang, Facile synthesis of hydroxyapatite/yeast biomass composites and their adsorption behaviors for lead (II), J. Coll. Inter. Sci. 477 (2016) 181-190. https://doi.org/10.1016/j.jcis.2016.05.050. [4] I. Ali, New generation adsorbents for water treatment, Chem. Rev. 112 (2012) 5073-5091. https://doi.org/10.1021/cr300133d. [5] B. Kizilkaya, A.A. Tekınay, Utilization to remove Pb(II) ions from aqueous environments using waste fish bones by ion exchange, J. Chem. 204 (2014) 1-12. http://dx.doi.org/10.1155/ 2014/739273. [6] F. Wang, Y. Guo, H. Wang, Facile preparation of hydroxyapatite with a three dimensional architecture and potential applicationin water treatment, Cryst. Eng. Comm. 13 (2011) 5634-5637. https://doi.org/10.1039/C1CE05485F. [7] A.R. Ibrahim, Y. Zhou, X. Li, Synthesis of rod-like hydroxyapatite with high surface area and pore volume from eggshells for effective adsorption of aqueous Pb2+, Mater. Res. Bull. 62 (2015) 132-141. http://dx.doi.org/10.1016/j. materresbull.2014.11.023. [8] L.C. Palmer, C.J. Newcomb, S.R. Kaltz, E.D. Spoerke, S.I. Stupp, Biomimetic systems for hydroxyapatite mineralization inspired by bone and enamel, Chem. Rev. 108 (2008) 4754-4783. https://do.org/10.1021/cr8004422. [9] T. Kaludjerovic, S. Raicevic, Aqueous Pb sorption by synthetic and natural apatite: kinetics, equilibrium and thermodynamic studies, Chem. Eng. J. 160 (2010) 503-510. https://doi.org/10.1016/j.cej.2010.03.061. [10] J. Cha, M. Cui, M. Jang, S.H. Cho, D.H. Moon, J. Khim, Kinetic and mechanism studies of the adsorption of lead onto waste cow bone powder (WCBP) surfaces, Environ. Geochem. Health. 33 (2011) 81-89. https://doi.org/ 10.1007/s10653 -010-9357-z. [11] R. Zhu, X. Lai, J.E. Halpert, R. Yu, D. Wang, Hierarchical hydroxyapatite microspheres composed of nanorods and their competitive sorption behavior for heavy metal ions, Euro. J. Inor. Chem. 16 (2012) 2665-2668. https://doi. org/10.1002/ejic.201101038. [12] T. Kokubo, H. Takadama, How useful is SBF in predicting in vivo bone bioactivity, Biomat. 27 (2006) 2907-2915. https://doi.org/10.1016/j. biomaterials.2006.01.017. [13] Y. Zhou, D. Chang, J. Chang, Preparation of nano-structured pig bone hydroxyapatite for high-efficiency adsorption of Pb2+ from aqueous solution, App. Ceram. Tech. 14 (2017) 1125-1133. https://doi.org/10.1111/ijac.12749. [14] JCPDS PDF card no. 09-432. [15] A.M. Nasser et al, Extraction of pure natural hydroxyapatite from the bovine bones bio waste by three different methods, J. Mater. Process. Tech. 209 (2009) 3408-3415. https://doi.org/ 10.1016/j.jmatprotec.2008.07.040. [16] S.M. Mousa, N.S. Ammar, H.A. Ibrahim, Removal of lead ions using hydroxyapatite nano-material prepared from phosphogypsum waste, J. Saudi. Chem. Soc. 20 (2016) 357-365. https://doi.org/10.1016/j.jscs.2014.12.006. [17] D. Wang et al, Facile fabrication of Pb(NO3)2/C as advanced anode material and its lithium storage mechanism, Electrochim. Acta. 120 (2014) 110-121. https://doi.org/10.1016/j. electacta.2013.12.080. [18] J. Wang et al, Spray pyrolyzed PbO/C nanocomposites as anode for lithium-ion batteries, J. Electrochem. Soc. 153 (2006) 787-793. https://doi.org/10.1149/1.2172570. [19] ASTM 05-0561 and 05-0570.